Local Governance Restructuring in Nepal: From Government to Governmentality - Acharya, Keshav K. (Dhaulagiri Journal of Sociology and Anthropology, 2018)
Local governments are the closest unit of the grassroots communities as they are not only undertaking to institutionalize the governance system and create enabling environment to promote the democratic values and public participation mainly from marginal section in decision making process, but also accelerate the economic development so that they enhance the peoples' capacity and enable them to influence the local governments representatives for responsive governance. However, Nepali society remains frustration and dissatisfaction at the citizen level, and dishonrization and dishonesty in the political and bureaucratic domain as these attributes have created the extreme risk to capacity development of the local governments. Against this perspective, the study aims to address a major research question: to what extent local governments are able to implement the constitutional granted exclusive and concurrent rights to transform the local communities, which is a consequence of governance shift from government to governmentality. Findings indicate that more capacity is required to institutionalize the restructuring process of local governance, increase citizen engagement in local governance system, build new partnerships in changing context, enhance technical, administrative, and fiscal capacity for effective service delivery, and formulate the essential laws, acts, and regulations. Nonetheless, some major arguments such effectiveness of local autonomy, political differences mainly identity based issues, productive role of outsiders, and democratization of bureaucratic assertiveness have been remained to be answered.